Penggunaan Metode SAW dalam Sistem Pendukung Keputusan Pemilihan Pegawai Terbaik - Lufti Puspitasari; Joni Maulindar; Vihi Atina (Infotek: Jurnal Informatika dan Teknologi, 2025)
This research aims to develop a website-based Decision Support System (DSS) to facilitate the selection of the best employees at the Ngrampal District Office. Employee performance assessments carried out manually have so far been considered less effective due to high subjectivity and a time-consuming process. The system built uses the Simple Additive Weighting (SAW) method which is able to give weight to each assessment criterion such as absenteeism, roll call attendance and employee performance. SAW was chosen because of its ability to provide objective ranking results based on measurable data. Implementation of this system shows faster and more accurate results in determining the best employees compared to manual assessments. Apart from improving the quality of performance appraisals, the implementation of this web-based system is also expected to motivate employees to improve their performance. This decision support system was created only within the scope of the Ngrampal District Office with three assessment criteria. It is hoped that this research can be developed further by adding new assessment criteria and applied in other agencies to expand the validity and effectiveness of the system